Cuban Historiography. Interview with Oscar Zanetti Lecuona - Lara, Martín (2016)
Interview with historian Óscar Zanetti, professor at the Universidad de La Habana. The interview reviews his academic development and main research topics. It focuses on several subjects concerning 20th century Cuban historiography, suchas the professionalization of the discipline, lines of research during the Cold War, infl uences, and current academic challenges in light of the restoration of diplomatic relations between Washington and La Habana.